Pendeteksian Sumber Air dalam Tanah untuk Memenuhi Kebutuhan Air Domestik di Desa Hargomulyo, Kecamatan Gedangsari, Kabupaten Gunungkidul - Akhmadi; Arya Pangestu Hidayat; Nina Alif Flour Rinda (Direktorat Pengabdian kepada Masyarakat, 2024)
Gunungkidul Regency, particularly Hargomulyo Village, is one of the areas affected by the long dry season this year. This sub-district faces a critical issue with the scarcity of clean water sources. Therefore, this research aims to estimate the potential of groundwater resources in the Hargomulyo sub-district to guide drilling efforts and meet domestic water needs. The methods used in this research are the Vertical Electrical Sounding (VES) method and the electromagnetic (EM) method to assess groundwater potential, while referring to SNI 6728:1:2015 concerning the preparation of spatial balances of natural resources to determine domestic water needs. The VES method was conducted in Jatibungkus and Mangli hamlets, while the EM method was carried out in Suruh hamlet. The VES method did not identify groundwater sources, whereas the EM method revealed groundwater sources with a discharge rate of 4,920 liters per hour. Domestic water needs in Hargomulyo District amount to 441,900 liters per day. The topography of Hargomulyo Village is predominantly hilly, making geoelectric methods less effective. The geoelectric method only detects underground rock materials, whereas in Hargomulyo Village, groundwater is stored in rock fractures, making it difficult for geoelectric methods to detect. To address this issue, the electromagnetic method is recommended. This method is quite effective in terrain dominated by hilly areas. The results of groundwater estimation using the EM method can fulfill some of the domestic water needs in Hargomulyo District. Repeated water detection using this method could meet domestic water needs and mitigate the water shortage problem in Hargomulyo District.